Assessing the Antecedents and Consequences of Experience Value in Online Education: A Quantitative Approach - Zhao, Hong; Song, Lijuan (Frontiers in Psychology, 2022)
The experience value of online education is a hot topic in both theoretical and practical circles, but research on its mechanism of action is limited. Therefore, this study systematically investi-gates the relationship between brand image, experience value and continuance intention through a theoretical analysis of brand image, and discusses the boundary role of effective commitment in it. In this study, 475 users were used to conduct structural equation modeling analysis. The re-sults of the study found that experience value had a positive and significant effect on user con-tinuance intention under the significant influence of brand image, but affective commitment did not play a positive moderating role in the relationship between experience value and continuance intention. This study examines the mechanism of the antecedents and consequences of experience value, and provides a new direction for the construction of online education and the development of online education and marketing strategies.